A descriptive analysis of anglicisms used in ecuadorian newspapers - García Mejía, Juanita (2010)
The Ecuadorian newspapers used to accomplish this research are seven national El Comercio newspapers, seven local Ultimas Noticas newspapers, and seven El Extra tabloids. All of these newspapers were published in the year 2009 in South America’s Ecuador. The ads, news, reports, social pages, and sports section of each of the above mentioned newspapers were analyzed. In order to carry out this analytic and descriptive research, all the 21 above mentioned newspapers were purchased. Then each newspaper was read entirely. Every anglicism found in the respective newspaper was highlighted and documented for further analysis.